Idiopathic neonatal hemoperitoneum presented as scrotal hematoma: it's a diagnostic challenge? - Salatto Alessia; Indrio Flavia; Campanella Vittoria; Maggipinto Cosetta; Cocomazzi Raffaella; Canale Francesco; Nobili Maria; Maffei Gianfranco; Bartoli Fabio (BMC, 2021)
Abstract Background Idiopathic hemoperitoneum in the newborn is an entity very rarely encountered in clinical practice. Case presentation A case of scrotal hemorrhage (SH) associated with intrabdominal hemorrhaging and acute anemia is presented. Indications for early surgery included a massive scrotal hematoma, rapid onset of severe anemia, and unknown etiology. Conclusion Clinical and diagnostic approaches in a case of neonatal scrotal hematoma should be given careful consideration as abdominal in origin, and a pre-operative computed tomography (CT) scan or magnetic resonance image (MRI) in addition to an abdominal/scrotal ultrasound should be added as part of the diagnostic work-up.